2020
DOI: 10.1126/sciadv.aay7031
|View full text |Cite
|
Sign up to set email alerts
|

Surrounded catalysts prepared by ion-exchange inverse loading

Abstract: The supported catalyst featuring highly dispersed active phase on support is the most important kind of industrial catalyst. Extensive research has demonstrated the critical role (in catalysis) of the interfacial interaction/perimeter sites between the active phase and support. However, the supported catalyst prepared by traditional methods generally presents low interface density because of limit contact area. Here, an ion-exchange inverse loading (IEIL) method has been developed, in which the precursor of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Additionally, the high‐resolution TEM (HRTEM) image in Figure 1e shows the lattice of Co 3 O 4 , i.e., the d‐spacings of 0.467 and 0.286 nm could be ascribed to the (111) and (220) facets of Co 3 O 4 , [3a] while the lattice of CeO 2 is difficult to observe. The energy‐dispersive X‐ray spectroscopy (EDS) elemental mappings of the hexagonal nanoparticle are shown in Figure 1f, and it is observed that Ce is uniformly distributed in the nanoparticle, implying sufficient contact between Ce and Co. For Co 3 O 4 /CeO 2 ‐IM, Figure 1g shows a TEM image of a random nanoparticle, while the HRTEM image in Figure 1h shows the lattices of both Co 3 O 4 and CeO 2 , i.e., a d‐spacing of 0.310 nm ascribed to the CeO 2 (111) facet [16] . Interestingly, the EDS elemental mappings of the nanoparticle (Figure 1i) show that the distribution of Ce in the nanoparticle is not uniform, with a sparse distribution in most regions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the high‐resolution TEM (HRTEM) image in Figure 1e shows the lattice of Co 3 O 4 , i.e., the d‐spacings of 0.467 and 0.286 nm could be ascribed to the (111) and (220) facets of Co 3 O 4 , [3a] while the lattice of CeO 2 is difficult to observe. The energy‐dispersive X‐ray spectroscopy (EDS) elemental mappings of the hexagonal nanoparticle are shown in Figure 1f, and it is observed that Ce is uniformly distributed in the nanoparticle, implying sufficient contact between Ce and Co. For Co 3 O 4 /CeO 2 ‐IM, Figure 1g shows a TEM image of a random nanoparticle, while the HRTEM image in Figure 1h shows the lattices of both Co 3 O 4 and CeO 2 , i.e., a d‐spacing of 0.310 nm ascribed to the CeO 2 (111) facet [16] . Interestingly, the EDS elemental mappings of the nanoparticle (Figure 1i) show that the distribution of Ce in the nanoparticle is not uniform, with a sparse distribution in most regions.…”
Section: Resultsmentioning
confidence: 97%
“…The energydispersive X-ray spectroscopy (EDS) elemental mappings of the hexagonal nanoparticle are shown in Figure 1f, and it is observed that Ce is uniformly distributed in the nanoparticle, implying sufficient contact between Ce and Co. For Co 3 O 4 /CeO 2 -IM, Figure 1g shows a TEM image of a random nanoparticle, while the HRTEM image in Figure 1h shows the lattices of both Co 3 O 4 and CeO 2 , i.e., a d-spacing of 0.310 nm ascribed to the CeO 2 (111) facet. [16] Interestingly, the EDS elemental mappings of the nanoparticle (Figure 1i) show that the distribution of Ce in the nanoparticle is not uniform, with a sparse distribution in most regions. results are shown in Figures S2 (full spectra) and S3 (deconvolutions).…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…55 In addition, the ion-exchange method can produce complicated heterostructures, core−shell structures, and metastable phases that are difficult to achieve via conventional methods. 46,56 Hao et al utilized the difference in solubility products (K sp ) to drive the substitution of Ni 2+ in the Ni(OH) 2 nanosheets (support precursor) with metal cations from the dissolved hydroxide precursors [Al(OH) 3 , Ce(OH) 3 , Cu(OH) 2 ], so as to prepare several Ni-based catalysts with various structures (e.g., core−shell, inverse structure, and gradient structure). 46 Zhao et al reported the preparation of single atom Ni catalyst supported on nitrogen-doped porous carbon (Ni SAs/N−C) via ionic exchange assisted by high-temperature etching between Zn nodes and Ni 2+ within the MOF cavities (Figure 4a).…”
Section: Sol−gel Methodmentioning
confidence: 99%
“…Additionally, because the overall particle morphology is maintained in cation exchange, this method is advantageous for preparing ionic nanocrystals with controlled morphology. 3 Moreover, cation exchange enables a wide range of materials to be synthesized including oxides, chalcogenides, and halides 4–7 as well as complex nanostructures such as alloys, 8 core/shells 9 and hollow 10 nanoparticles, and segmented architectures 11 by rapid and low-temperature cation-to-cation transformations. 12 However, ion exchange has been limited to particular materials such as metal chalcogenide and ionic metal oxide crystals composed of cation and anion constituents.…”
Section: Introductionmentioning
confidence: 99%